1984
DOI: 10.1021/om00084a019
|View full text |Cite
|
Sign up to set email alerts
|

Aryl group interchange between triarylphosphines catalyzed by Group VIII transition metals

Abstract: CH3CN)2MoBr(CO)2(7)3-C8H13)], 81923-03-7; (+)-[NMCpMo-(NO)(CO)(i/3-C8H13)]BF4, 89689-90-7; (+)-[NMCpMo(NO)-(CO)(i73-C8H13)]PF6, 89772-14-5; (-)-[NMCpMo(NO)(CO)(7,3-C8H13)]BF4, 89771-47-1; (+)-NMCpMo(NO)(Br)(7,3-C8H13), 89689-91-8; (-)-NMCpMo(NO)(Br)(r)3-C8H13), 89771-48-2; (-)D-NMCpMo(NO) (CO) (7j2-C8H13OH), 89689-92-9; (-)D-NMCpMo-(NO)(CO)(tj2-C8H13D), 89689-93-0; Mo(CO)6,13939-06-5; NOBF4, 14635-75-7; NaBr, 7647-15-6; 3-bromocyclooctene, 7422-06-2;(-)-cycloocten-3-ol, 62210-83-7; (-)-3-deuteriocyclooctene, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Actually, literature precedent has often shown the reversible nature of this P-C bond cleavage and forming. As mentioned above, in 1984, two independent works reported that a P-C/P-C cross-metathesis reaction is a reversible process which seems to proceed through oxidative addition and consecutive reductive elimination by Pd(0) in both cases [34][35]. Inspired by these works, Morandi and coworkers systematically studied both the forward and the reverse reaction of a range of meta-and para-substituted triarylphosphines with PPh3 using both catalytic amount of Pd(0) and PhI.…”
Section: Scheme 55mentioning
confidence: 95%
See 3 more Smart Citations
“…Actually, literature precedent has often shown the reversible nature of this P-C bond cleavage and forming. As mentioned above, in 1984, two independent works reported that a P-C/P-C cross-metathesis reaction is a reversible process which seems to proceed through oxidative addition and consecutive reductive elimination by Pd(0) in both cases [34][35]. Inspired by these works, Morandi and coworkers systematically studied both the forward and the reverse reaction of a range of meta-and para-substituted triarylphosphines with PPh3 using both catalytic amount of Pd(0) and PhI.…”
Section: Scheme 55mentioning
confidence: 95%
“…In 1984, Bryant et al discovered the intermolecular aryl scrambling of triarylphosphines when using several transition metals (e.g. Rh, Co, Os, Ni, Pd, and Ru) as catalysts with two different kinds of triarylphosphines (Scheme 4) [34]. The reaction mixture has shown complete equilibration between reactants and products.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To develop more efficient catalytic reactions, the fundamental behavior of triarylphosphine in the presence of a transition‐metal catalyst must be understood. Abatjoglou and Bryant studied Group VIII transition‐metal‐catalyzed C aryl −P bond metathesis (Scheme ) . Different from aforementioned partial utilization of phosphine through C−P bond activation, their findings suggested that both the cleaved aryl moiety and phosphino moiety could be used as building blocks at the same time.…”
Section: Transformation Involving Both C‐ and P‐moietiesmentioning
confidence: 99%